Closing Gender Gaps in Farmers’ Access to Climate Information: The Case of Radio Listeners Clubs (RLCs) in Rwanda: Preliminary results of a mixed-method analysis - Ingabire, Chantal (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate change and variability remain a serious challenge to the agricultural sector, and their impacts are unevenly spread, with certain individuals, groups, communities, and regions being disproportionately affected. Farming communities, especially smallholder poor farmers, are among the most vulnerable groups. This is not gender neutral. Gender disparities inherent in most of these communities tend to impact individuals’ capacity to combat and build resilience to the adverse effects of climate change. Women farmers are more affected than men due to inequitable access and control of productive resources as well as unequal intra-household power relations that limit their ability to adapt to climate variability and change. Their limited access to supporting services and time poverty due to unbalanced gender roles also limit their resilience to shocks, keeping them in a climate vulnerability trap. Access to climate information is a key element in building farmers’ preparedness and resilience to climate change and variability. However, it is often also shaped by social norms that restrict women’s attendance in meetings and participation in trainings, the unpaid labor that leads to their low interactions in public spheres as well as low contact with agricultural advisory services and membership in various forms of collective actions. Limited access and control of communication assets like mobile phones, television, and radio also contribute to women’s low access to climate information.